Akses listrik, air minum, dan sanitasi serta modal manusia di Indonesia - Chrisnahutama, Adrian (Journal of Economics Research and Policy Studies, 2023)
A country is said to be prosperous if it has the quality of human capital to carry out the production process. According to the Cobb-Douglas production function, the output (Q) of a country is explained by the input functions of artificial capital (K) and labor capital (L). Labor capital will be optimal if a country has quality human capital. Quality human capital will be achieved with good health and education levels. This study aims to analyze the influence of access to electricity, drinking water, and sanitation on Indonesia's quality of human capital in 2010–2019. The quality of human capital in this study is measured using the Human Development Index (HDI). The results of this study show that these three infrastructures have a significant positive effect on human capital. Thus, equal provision of these three accesses is a necessary and sufficient condition for improving the welfare of a country.